Nigerian and Ghanaian women working in the Brussels red-light district - Adeyinka, Sarah, ....-; Samyn, Sophie, ....-; Zemni, Sami, 1972- (London : Routledge, Taylor & Francis Group, 2021)
"This book unravels the lives, needs and experiences of Nigerian and Ghanaian women working in prostitution in Brussels. This volume casts a light on the working conditions and the experiences of 38 women of Nigerian and Ghanaian origin, whose daily struggles and challenges are recalled from interviews in the field. Working within the red-light district of Brussels, an area with high crime rates and lacking in basic healthcare provision, the women are faced with a number of issues on a daily basis, ranging from security and health-related concerns, to work-related stress, discrimination and perceived stigma. Full voice is given to their stories, as well as contributions from state actors and local inhabitants, with the chief aim of building safe and healthy places for both residents and workers alike. The authors conclude in presenting clear recommendations and tools for practitioners and policy makers, designed to improve the outcomes of migrant women working not just within the red-light district of Brussels, but also within wider European and global contexts. This book will be of particular interest for researchers and students of Migration Politics, Development Studies, Social Work and Sociology, as well as a useful guide for policy makers and practitioners in the field"--
Includes bibliographical references and index.
Keywords: Seksindustry ; Belgium; Prostitution ; Belgium; Human trafficking -- Ghana; Human trafficking -- Nigeria